Interseasonal RSV infections in Switzerland – rapid establishment of a clinician-led national reporting system (RSV EpiCH) (Swiss Medical Weekly, 2021)
In anticipation of an interseasonal respiratory syncytial virus (RSV) epidemic, a clinician-led reporting system was rapidly established to capture RSV infections in Swiss hospitals, starting in January 2021. Here, we present details of the reporting system and first results to June 2021. An unusual epidemiology was observed with an interseasonal surge of RSV infections associated with COVID-19-related non-pharmacological interventions. These data allowed real-time adjustment of RSV prophylaxis guidelines and consequently underscore the need for and continuation of systematic nationwide RSV surveillance.